The Issues of ESP Instruction for University Level in Indonesia - Farnia Sari (Universitas Indo Global Mandiri, 2018)
AbstractEnglish can be due to demand of Indonesian in the field of business, technology, education, and research. The implementation of ESP has revealed some factors, such as students, teachers, and ESP materials that have significant influences on the quality of teaching and learning ESP. These factors require serious attention from stakeholders and ESP practitioners to improve the quality of ESP instruction. The government language policy might emphasize the curricula of formal schools and teachers training for ESP instruction. The quality of teacher of ESP is high contributing to accommodate the teaching and learning ESP course. Besides that, the materials of ESP should be formulated by practitioners of ESP who had knowledge of ESP instruction and the aim of ESP might concern on the improvements in students' proficiency in English. Thus, the students are being better in academic and professional in the work domain. Keywords : Implementation, ESP instruction, the students, the teachers, the material development AbstrakBahasa Inggris dapat disebabkan oleh permintaan bahasa Indonesia di bidang bisnis, teknologi, pendidikan, dan penelitian. Pelaksanaan ESP telah mengungkapkan beberapa faktor, seperti siswa, guru, dan materi ESP yang memiliki pengaruh signifikan terhadap kualitas pembelajaran dan pembelajaran ESP. Faktor-faktor ini memerlukan perhatian serius dari para pemangku kepentingan dan praktisi ESP untuk meningkatkan kualitas instruksi ESP. Kebijakan bahasa pemerintah mungkin menekankan kurikulum sekolah formal dan pelatihan guru untuk instruksi ESP. Kualitas guru ESP berkontribusi tinggi untuk mengakomodasi pengajaran dan pembelajaran mata pelajaran ESP. Selain itu, materi ESP harus dirumuskan oleh praktisi ESP yang memiliki pengetahuan tentang instruksi ESP dan tujuan dari ESP mungkin berkaitan dengan peningkatan kemampuan siswa dalam bahasa Inggris. Dengan demikian, para siswa menjadi lebih baik di bidang akademik dan profesional dalam domain kerja.Kata kunci : Implementasi, instruksi ESP, siswa, guru, pengembangan materi